Considerations about tutoring in the postgraduate course of Family Medicine - Rubén Darío García Núñez; María Aurelia San Juan Bosch; Esteban Jesús Sánchez Martínez; Ibis Hernández Palet (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The tutorial function is an integrating part of the teaching practice and quality factor of postgraduate education. This review aims at characterizing the tutor´s and mentoring work as key elements for training competent specialists in the postgraduate course in Family and Community Medicine. For this, the most current aspects of in-service tutoring were reviewed, as well as the tutor's functions, which allowed authors to confirm that the distance to be followed is still long to achieve a correct in-service tutoring that allows a comprehensive training of postgraduates. It was concluded that family medicine tutors have not been sufficiently prepared to practice their profession as professors, so specific training is needed in this area, which is also a need felt by tutors and expressed in many meetings they have participated in.